Ethical and effective teaching at higher education - Mohamad, Souad A. (2011)
As we all know, some universities have paid less attention to the ethics of teaching than to research ethics. This article reflect an attempt to elucidate the importance of practicing ethical principles in college and university teaching in order to developing faculty and students' commitment to ethical teaching practices at the university level by understanding and honoring the special relationship between teachers and students and by considering practical guidelines of ethical college and university teaching skills to govern an effective teaching process.